The c-Abl tyrosine kinase phosphorylates the Fe65 adaptor protein to stimulate Fe65/amyloid precursor protein nuclear signaling. - MCLOUGHLIN, DECLAN (American Society for Biochemistry and Molecular Biology, 2004)
The amyloid precursor protein (APP) is proteolytically processed to release a C-terminal domain that signals to the nucleus to regulate transcription of responsive genes. The APP C terminus binds to a number of phosphotyrosine binding (PTB) domain proteins and one of these, Fe65, stimulates APP nuclear signaling. Fe65 is an adaptor protein that contains a number of protein-protein interaction domains. These include two PTB domains, the second of which binds APP, and a WW domain that binds proline-rich ligands. One ligand for the Fe65WW domain is the tyrosine kinase c-Abl. Here, we show that active c-Abl stimulates APP/Fe65-mediated gene transcription and that this effect is mediated by phosphorylation of Fe65 on tyrosine 547 within its second PTB domain. The homologous tyrosine within the motif Tyr-(Leu/Met)-Gly is conserved in a variety of PTB domains, and this suggests that PTB tyrosine phosphorylation occurs in other proteins. As such, PTB domain phosphorylation may represent a novel mechanism for regulating the function of this class of protein.
PUBLISHED
Keywords: Psychiatry